Personalized Human Papillomavirus Vaccination for Persistence of Immunity for Cervical Cancer Prevention: A Critical Review With Experts' Opinions - Chambuso, Ramadhani Salum; Rebello, George; Kaambo, Evelyn (Frontiers in Oncology, 2020)
The development of cervical cancer has been shown to involve both viral and host factors. The host factors are those that determine the specific response to human papillomavirus (HPV) infection by the patient’s immune system. The immune responses to vaccines have been shown to be influenced by polymorphisms in genes involved in innate and adaptive immunity. The specific genetic variants that may influence the immune responses to HPV vaccine which may contribute to persistence of immunity (POI) have not been widely studied yet. In order to address the question as to “is it right to vaccinate all children, and all with equal dose?” we have critically examined the knowledge of common immunogenetic and immunogenomic variations that may influence the HPV vaccine POI across various populations. We have also identified a number of specific research questions that need to be addressed in future research into host molecular genetic variations and HPV vaccine POI in order to afford life-long protection against the development of cervical cancer. This work informs future insights for improved HPV vaccine designs based on common host molecular genetic variations.